Field efficacy of premix formulation fipronil 5% + isoprothiolane 28% EC against yellow stem borer, brown plant hopper and blast disease of rice - Sarkar, P K; Roy, Debashis; Nath, P S (Indian Journal of Plant Protection, 2020)
Field effectiveness of pre-mix formulation of insecticide and fungicide (fipronil 5% + isoprothiolane 28% EC) at four different dosages, were evaluated against rice yellow stem borer (Scirpophaga incertulas), brown plant hopper (Nilaparvata lugens) and blast disease (Magnaporthe grisea) in comparison to standard checks fipronil 5% SC, chlorpyrifos 20% EC, isoprothiolane 40% EC and difenoconazole 25% EC during Kharif 2013 and 2014 at Studentsâ€™ Instructional Farm, Bidhan Chandra Krishi Viswavidyalaya, West Bengal, India, with a promising rice cultivar, Swarna Masuri. Fipronil 5% + isoprothiolane 28% EC at 330 and 495 g a.i./ha was found most effective with minimum per cent dead hearts(0.0-2.5% and 0.0-2.2%, respectively) and white ears (2.3, 3.0% and 2.0, 2.5%,Â respectively) consistently during the two seasons. The same treatments were effective against brown plant hopper also, with 75.8-88.2 and 77.0-89.2 per cent reduction while, leaf and neck blast were reduced by 83.5-100.0 and 87.06-100.00 per cent, respectively. Highest grain yield (46.1 and 45.5 q/ha) was obtained in the highest dosage of fipronil 5% + isoprothiolane 28% EC (330 g a.i./ha) with most favourable benefit: cost ratio (9.89 : 1). The test combination found relatively safe towards parasitoids and predatory population of wolf spiders and green mirid bugs. Hence, the novel pre-mix formulation of fipronil 5% + isoprothiolane 28% EC may be considered as an important addition to the existing chemicals for the IPM of rice insects and disease component.